Astragaloside IV Enhances Melanogenesis via the AhR-Dependent AKT/GSK-3β/β-Catenin Pathway in Normal Human Epidermal Melanocytes - Liu, Baoyi (Evid Based Complement Alternat Med, 2020)
Astragalus membranaceus root has been widely used for repigmentation treatment in vitiligo, but its mechanism is poorly understood. We sought to investigate the effect of astragaloside IV (AS-IV), a main active extract of the Astragalus membranaceus root, on melanin synthesis in normal human epidermal melanocytes (NHEMs) and to elucidate its underlying mechanisms. Melanin content, tyrosinase activity, qPCR, western blot, and immunofluorescence were employed. Specific inhibitors and small interfering RNA were used to investigate the possible pathway. AS-IV stimulated melanin synthesis and upregulated the expression of melanogenesis-related genes in a concentration-dependent manner in NHEMs. AS-IV could activate the aryl hydrocarbon receptor (AhR), and AS-IV-induced melanogenesis was inhibited in si-AhR-transfected NHEMs. In addition, we showed that AS-IV enhanced the phosphorylation of AKT and GSK-3β and nuclear translocation of β-catenin. AS-IV-induced MITF expression upregulation and melanin synthesis were decreased in the presence of β-catenin inhibitor FH353. Furthermore, AhR antagonist CH223191 inhibited the activation of AKT/GSK-3β/β-catenin signaling, whereas the expression of CYP1A1 (marker of AhR activation) was not affected by the AKT inhibitor in AS-IV-exposed NHEMs. Our findings show that AS-IV induces melanogenesis through AhR-dependent AKT/GSK-3β/β-catenin pathway activation and could be beneficial in the therapy for depigmented skin disorders.